2009
DOI: 10.1002/rmv.612
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus receptors: implications for tropism, treatment and targeting

Abstract: Adenoviruses (Ads) are the most frequently used viral vectors in gene therapy and cancer therapy. Obstacles to successful clinical application include accumulation of vector and transduction in liver cells, coupled with poor transduction of target cells and tissues such as tumours. Many host molecules, including coagulation factor X, have been identified and suggested to serve as mediators of Ad liver tropism. This review summarises current knowledge concerning these molecules and the mechanisms used by Ads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
111
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 123 publications
3
111
0
Order By: Relevance
“…Interestingly, some Ads of species D, including Ad8, Ad37, Ad19a [recently renamed Ad64 (2)], and the more recently sequenced Ad53, Ad54, and Ad56 (2,4,5), cause a distinct disease, epidemic keratoconjunctivitis (EKC) (6). Surprisingly, this specific pathogenesis in the eye contrasts with the rather ubiquitous receptor profile of EKC-causing Ads (7,8), and thus is likely linked to selective events occurring postattachment, such as differential triggering of innate and adaptive immune responses (3,9,10). Thus, differential immunomodulatory functions encoded in early transcription unit 3 (E3) may play an important role in disease (9,11).…”
mentioning
confidence: 99%
“…Interestingly, some Ads of species D, including Ad8, Ad37, Ad19a [recently renamed Ad64 (2)], and the more recently sequenced Ad53, Ad54, and Ad56 (2,4,5), cause a distinct disease, epidemic keratoconjunctivitis (EKC) (6). Surprisingly, this specific pathogenesis in the eye contrasts with the rather ubiquitous receptor profile of EKC-causing Ads (7,8), and thus is likely linked to selective events occurring postattachment, such as differential triggering of innate and adaptive immune responses (3,9,10). Thus, differential immunomodulatory functions encoded in early transcription unit 3 (E3) may play an important role in disease (9,11).…”
mentioning
confidence: 99%
“…[6] There are over 100 adenoviral serotypes identified that can infect and replicate in a wide range of organs, including 51 classified into six subgroups (A-F). [38,39] Of these, serotypes 2 and 5 in subgroup B are the most characterized viruses.…”
Section: Adenoviral Vectors-mentioning
confidence: 99%
“…Seven polypeptides form this complex capsid: hexon (II), penton base (III), fiber (IV), IIIa, VI, VIII, and IX (Campos & Barry, 2007;Sharma et al, 2009). The cell receptor depends on the virus subgroup: A, E and F subgroups use the cell surface coxsackievirus B and adenovirus receptor (CAR); B1 and B2 subgroups use CD46, CD80/86, receptor X, or heparan sulfate proteoglycan (HSPG); C subgroup uses CAR, HSPG, MHC-I, vascular cell adhesion molecule-I (VCAM-I), or integrins; and D subgroup uses CAR, sialic acid, or CD46 (Arnberg, 2009;Campos & Barry, 2007;Sharma et al, 2009). Adenoviral vectors have been used as tools for gene therapy since the late 80s (Friedmann, 1992), and the first clinical trial was started in 1993 (Douglas, 2007).…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…Furthermore, AdV2 and AdV5 have high bloodstream stability with a reduced risk of insertional mutagenesis, since their genome remains extrachromosomal (Douglas, 2007;Edelstein, 2007;Volpers & Kochanek, 2004). Nonetheless, several drawbacks have been identified during in-vivo evaluation of these vectors: (i) presence of pre-existing antibodies that rapidly neutralize the vector, (ii) after intravenous administration the vector is mainly taken up by liver cells, limiting the vector to reach its target tissue in adequate concentrations, and (iii) use of high doses in an effort to overcome these problems has not proven to be an adequate and safe approach (Arnberg, 2009). Three strategies can be used to solve these issues: (i) use of vectors from other subgroups different from AdV2 and AdV5 (subgroup C), (ii) use of non-human serotypes, and (iii) retargeting of the vector to cells or tissues of interest (Arnberg, 2009).…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation